2000
DOI: 10.1017/s026505170000022x
|View full text |Cite
|
Sign up to set email alerts
|

Music technology inspected: good teaching in Key Stage 3

Abstract: How is information and communications technology (ICT) used to promote musical learning by pupils aged eleven to fourteen, i.e. pupils in Key Stage 3? Inspectors from the Office for Standards in Education (OFSTED) visited 52 schools in England, and inspected 161 Key Stage 3 music lessons that made some use of ICT. This article describes the characteristics of the good teaching found in 106 of those lessons, and discusses some issues concerning the use of ICT in classrooms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 0 publications
0
13
0
5
Order By: Relevance
“…In conclusion, as the present report represents a snapshot of a small selection of schools, its results cannot be generalised. The investigation, following Mills & Murray's (2000) more extensive work, preceded recent curricular developments which suggest that music technology may be getting a stronger pro®le in English schools and that it will become a more prevalent feature of the work of music teachers (cf. Kwami, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, as the present report represents a snapshot of a small selection of schools, its results cannot be generalised. The investigation, following Mills & Murray's (2000) more extensive work, preceded recent curricular developments which suggest that music technology may be getting a stronger pro®le in English schools and that it will become a more prevalent feature of the work of music teachers (cf. Kwami, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Early work examined the emerging use of and access to technological resources in the music classroom (Bray, 1997;Naughton, 1997;Rogers, 1997;Salaman, 1997), implications for teacher training (Hunt and Kirk, 1997) and potential applications for students with profound learning disabilities (Ellis, 1997). By 2000, inspections of 106 music classrooms found a high degree of technology use, emphasizing that good practice stemmed from a knowledge of how the technology functioned, ability to model use of the technology, and minimized time loss from setup (Mills and Murray, 2000). In the United Kingdom, a 2003 government report found that 24% of secondary teachers were making substantial use of technology in their classrooms, and 30% reported a positive effect on their teaching (DfES, 2005) The demonstrated benefits of these tools in the classroom led to calls for technology-based professional development workshops (Bauer et al, 2003), and teachers continued to develop strategies to incorporate the available tools at the time-recording, editing, playback, early web-based resources and videos-into their practices (Ho, 2004;Anderson and Ellis, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Mills and Murray (2000) assert that technology could enhance music lessons when students worked primarily as musicians. This alternate approach was also supported by Bray, Brown, and Green (2004) who suggested that, ICT has the potential to enhance creativity, facilitate learning, and encourage exploration and independent learning.…”
Section: Discussionmentioning
confidence: 99%